Cellular Effects of Heavy Metals 2011
DOI: 10.1007/978-94-007-0428-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Toxicity in an Insect Cell Line (Methyl-HgCl, HgCl2, CdCl2 and CuSO4)

Abstract: We have analyzed the toxicity, uptake and intracellular effects of CdCl 2 , HgCl 2 , MeHgCl and CuSO 4 in a cell line of the Asian tiger mosquito Aedes albopictus. Cell proliferation was drastically inhibited by CdCl 2 and MeHgCl while HgCl 2 showed only a moderate effect. Acute toxicity tests showed that membrane integrity was severely affected in cells treated with low doses of HgCl 2 and MeHgCl. Uptake of both mercury species occurred via simple diffusion while cadmium entered the cells through mediated tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
2
2
0
Order By: Relevance
“…For example, in a coccinellid beetle (Coleoptera) feeding on a nickel hyperaccumulator plant, apoptosis, necrosis, and autophagy were identified with the elimination of excess metals, maintaining homeostatic conditions (Rost-Roszkowska et al, 2008). CuSO 4 -treated cells of tiger mosquitoes showed massive apoptosis characterized by nuclear heterochromatin condensation (Braeckman, 2011), a phenomenon which was interestingly found also here in urban wasps. Heterochromatin has been associated with several functions, from gene regulation to the protection of the integrity of chromosomes, and a high density could suggest a general less efficient transcription and epigenetic silence (i.e., repression of nearby sequences) (Grewal & Jia, 2007).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, in a coccinellid beetle (Coleoptera) feeding on a nickel hyperaccumulator plant, apoptosis, necrosis, and autophagy were identified with the elimination of excess metals, maintaining homeostatic conditions (Rost-Roszkowska et al, 2008). CuSO 4 -treated cells of tiger mosquitoes showed massive apoptosis characterized by nuclear heterochromatin condensation (Braeckman, 2011), a phenomenon which was interestingly found also here in urban wasps. Heterochromatin has been associated with several functions, from gene regulation to the protection of the integrity of chromosomes, and a high density could suggest a general less efficient transcription and epigenetic silence (i.e., repression of nearby sequences) (Grewal & Jia, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…In the tiger mosquito Aedes albopictus Skuse (Diptera), metals such as Cd and Hg induce intracellular pathologies similar to those found in P. dominula from the urban sites, i.e. mitochondrial alterations, nuclear deformation and increased lysosomal profiles (Braeckman, 2011). We also found great cytoplasm vacuolization in the urban wasps.…”
Section: Discussionmentioning
confidence: 99%
“…The irregulation of the nuclear envelopes and karyorrhexis indicate a pathway of cell death [87,88]. Some authors attributed apoptosis to metal accumulation [89,90], which is in agreement with our results. Research has proven the relation between exposure to metals and the prevalence of apoptosis [91,92].…”
Section: Plos Onesupporting
confidence: 93%
“…Based on our results, we suggest that Cd exposure in larvae may result in gametic damage in both male and female adults, and the inhibition of mating behavior and fecundity of adults in O. furnacalis. Previous studies showed that the early formation, growth, and differentiation of egg formation begin in the larval stage [47] and Cd exposure could cause some general intracellular pathologies in insect cells [48,49]. We hypothesize that Cd exposure may cause irreversible damage in larvae cells, and this damage may also persist into adulthood, leading to gametic damage in adults.…”
Section: Discussionmentioning
confidence: 83%